SISTEM PENYUSUNAN LAPORAN KEUANGAN MENGGUNAKAN STANDAR AKUNTANSI KEUANGAN (SAK) - Atika Atika; Mentari Ghozalia Khairunissa; Andi Fatmawati (Budgeting: Jurnal Akuntansi Syariah, 2021)
Financial Statements are the main means of financial information for parties outside the company. The results of the financial statements themselves are in the form of an accounting process that can be used as a communication tool between financial data and the activities of a company and parties with an interest in the data or activities of the company. Financial statements according to Financial Accounting Standards (SAK) are very important in the company, The important purpose of financial statements according to Financial Accounting Standards (SAK) is to ensure financial position, profitability and performance, determine cash flows, find out the results of transactions within the company, provide related information financial resources and obligations to be completed, directing accounting policies and checking the efficiency and effectiveness of the Company's management.